Kartogenin‐Loaded Aminated Hollow Mesoporous Prussian Blue Nanozyme‐Reinforced Hydrogel Remodels the Senescent Microenvironment via Reactive Oxygen Species Scavenging and Stimulator of Interferon Genes Inhibition to Promote Cartilage Regeneration - Shu‐Hang He; Zhi‐Han Shen; Ren Zhang; Po‐Lin Liu; Xu‐Ran Li; Qing‐Song Deng; Yu‐Chen Zhang; Ang Wang; Xiao‐Qiu Dou; Shang‐Chun Guo; Shi‐Cong Tao (Small Structures)
Articular cartilage defects remain an intractable clinical challenge due to the limited capacity of cartilage for self‐renewal and repair. Excessive accumulation of reactive oxygen species (ROS) leads to mitochondrial dysfunction, inflammation, and chondrocyte senescence, impeding cartilage regeneration. In this study, we developed an injectable, dual‐function hydrogel system comprising kartogenin (KGN)‐loaded aminated hollow mesoporous Prussian blue (NH2‐HMPB) nanozyme (termed NH@K nanozyme) and hyaluronic acid methacrylate (HAMA). This “double sustained‐release” system prolongs the therapeutic duration of KGN while seamlessly filling irregular cartilage defects. As NH@K nanozyme is released, it scavenges ROS, reduces oxidative stress, protects mitochondrial function, inhibits cyclic GMP‐AMP synthase–stimulator of interferon genes (STING) pathway activation, and modulates inflammation and macrophage polarization, rejuvenating the senescent microenvironment. RNA sequencing analysis and in vitro experiments revealed that NH@K nanozyme modulates signaling pathways associated with chondrogenesis and inflammation, promoting cartilage repair. In a rat model, HAMA‐NH@K hydrogel significantly enhances extracellular matrix deposition and cartilage regeneration. The synergistic combination of nanozyme and hydrogel in our system enables the reshaping of the senescent microenvironment, providing a promising strategy for advanced cartilage regeneration.